2007
DOI: 10.1021/ma062199r
|View full text |Cite
|
Sign up to set email alerts
|

Tunable pH- and Temperature-Sensitive Copolymer Libraries by Reversible Addition−Fragmentation Chain Transfer Copolymerizations of Methacrylates

Abstract: Reversible addition-fragmentation chain transfer (RAFT) polymerizations have been performed on a Chemspeed Accelerator SLT100 automated synthesizer to polymerize N,N-(dimethylamino)ethyl methacrylate (DMAEMA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA) at 70 °C. Azobis(isobutyronitrile) (AIBN) was used as source of radicals and 2-cyano-2-butyl dithiobenzoate (CBDB) as RAFT agent. A complete screening in composition of P(DMAEMA-stat-PEGMA) copolymers was elaborated from 0% of PEGMA to 100% of PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
308
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(332 citation statements)
references
References 55 publications
18
308
0
Order By: Relevance
“…Symmetrical trithiocarbonates are frequently synthesized from the corresponding halide, and carbon disulfide in the presence of a base. Aoyagi and Endo [290] have shown that this process can be performed on benzyl halides, and stoichiometric carbon disulfide at low temperature (40 • C) in air with potassium bicarbonate as base to provide near quantitative yields of the corresponding dibenzyl trithiocarbonates (111)(112)(113)(114).…”
Section: Synthesis Of Raft Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetrical trithiocarbonates are frequently synthesized from the corresponding halide, and carbon disulfide in the presence of a base. Aoyagi and Endo [290] have shown that this process can be performed on benzyl halides, and stoichiometric carbon disulfide at low temperature (40 • C) in air with potassium bicarbonate as base to provide near quantitative yields of the corresponding dibenzyl trithiocarbonates (111)(112)(113)(114).…”
Section: Synthesis Of Raft Agentsmentioning
confidence: 99%
“…[114,115,251] High throughput methods have been applied to synthesize libraries of methacrylate polymers (MAA, various oligo(ethylene glycol) methacrylates and copolymers of MAA with PEGMA, [108] MMA, DMAEMA and block and statistical copolymers, [114] and copolymers of DMAEMA with PEGMA [113] ) for evaluating the composition dependence of the lower critical solution temperature (LCST).…”
Section: Reaction Conditions (Initiator Temperature Pressure Solvementioning
confidence: 99%
“…The LCST of such a polymer can be affected by many parameters, including molecular weight [50,51], polymer composition [9,52,53], solution concentration [50], and pH [8,9] in the case of PDMAEMA. Because the DMAEMA/styrene copolymerizations using NHS-BlocBuilder were relatively controlled as demonstrated earlier, final copolymers obtained have similar M n (10.4 ± 0.9 kg mol −1 ) and PDI (1.42 ± 0.12).…”
Section: Studies Of Temperature and Ph Sensitivities Of Copolymers Inmentioning
confidence: 99%
“…It exhibits a lower critical solution temperature (LCST)-type phase separation upon heating at neutral or basic conditions and is completely water-soluble in acidic media [8][9][10]. To fine-tune the transition conditions and polymer properties, DMAEMA has been incorporated into block copolymers with various counter blocks such as the pH-sensitive poly(2-vinyl pyrindine) to obtain pH-dependent micelles [8], a temperature-responsive block such as POEGMA [9] and PNIPAM [11] to alter the LCST, and a hydrophobic block such as poly(2-(N-carbazolyl)ethyl methacrylate) to make amphiphilic diblock copolymers with hole-transport properties [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation